P1-4 Cancer rehabilitation in palliative care. (13th February 2023) - Fu, Jack
Abstract : Cancer rehabilitation and supportive care are two specialties dedicated to improving quality of life in oncology. The two specialties possess services that could potentially benefit advanced cancer patients suffering from significant symptom burden. At MD Anderson Cancer Center, this patient population is often seen by both specialties. This presentation will highlight areas for cooperation between the specialties. At the crossroads of prognosis, performance status and cancer treatment, cancer rehabilitation specialists often encounter advanced cancer patients when they have suffered a decline in their performance status. Oncology treatment can be withheld until a patient's performance status improves adequately. The effectiveness of rehabilitation interventions in improving function and mobility can impact whether a patient receives additional oncology treatment. Cancer symptoms can affect performance status and physical functioning. Strong evidence exists that physical activity improves cancer related symptoms including reducing anxiety, depression, and fatigue and increasing quality of life with few side effects and little cost compared to medications. Cancer rehabilitation specialists are experts at exercise and can guide cancer patients through an exercise program while addressing symptoms and minimizing musculoskeletal complications. Furthermore, physiatrists are experts at treating musculoskeletal sources of pain and dysfunction which can assist supportive care physicians in managing pain potentially reducing the need for opiates and their side effects. Besides prescribing physical therapy, physiatrists are able to perform injections (such as joint injections and muscle relaxant injections) and prescribe pain medications. Physiatrists are also experienced in treating other symptoms frequently experienced by cancer patients such as constipation, fatigue and cognitive dysfunction. Palliative cancer rehabilitation can be incredibly valuable to patients at the end of life. By working with terminal cancer patients and their caregivers, cancer rehabilitation specialists can enable patients with advanced terminal disease to experience meaningful events such as enabling discharge from an inpatient setting to see friends and family members or attend important events such as a wedding or family reunion. While significant progress has been made, cancer rehabilitation continues to suffer from under-recognition and under-referral by oncologists. These obstacles are similar to those that our counterparts in palliative care have made tremendous recent strides in overcoming. The path for cancer rehabilitation to become standard of care for cancer patients throughout the cancer care continuum including at the end of life will come through proving the efficacy of our interventions through increased research, integrating into clinical practice guidelines, building clinical capacity, and advocating for public policy change. The utilization of costly services at the end of life is often questioned. Research pertaining to palliative cancer rehabilitation interventions have demonstrated improved function and decreased need for caregiver assistance. However, more research regarding cancer rehabilitation interventions at the end of life are urgently needed in particular to demonstrate our impact on cost and clinical outcomes.